The Care of the Uninsured in America - Johnson, Nancy J.; Johnson, Lane P. (Springer New York : Imprint: Springer, 2010)
The Care of the Uninsured in America Edited by Nancy J. Johnson, El Rio Community Health Center, Tuscon, AZ Lane P. Johnson, Arizona Health Science Center, Tucson, AZ They earn too much for Medicaid but not enough to afford a health plan. Or their employer rescinded their benefits. Or they're "not disabled enough" for disability. Some 45 million people have fallen through the cracks of America's health care system, and this lack of coverage affects access to coverage, timeliness of care-even life expectancy. The Care of the Uninsured in America presents a nuanced portrait of this broad population-urban and rural, from generational poverty and the working poor-while illuminating the current state of medical/dental insurance and the circumstances that cause so many to do without. Its authors conceptualize lack of insurance as a health disparity (as are ethnicity, gender, age, etc.), and explain its collective health impact and major issues involved in providing care. In clear, useful prose, the book: Identifies subpopulations among the uninsured (e.g., the mentally ill, the homeless, people with HIV) and their specific care needs. Outlines necessary skills and strategies for working with uninsured patients, from health promotion to cultural competency. Offers models and case examples of innovative care programs. Reports on methods for improving access and support, including coalition building and health information management. Describes medication assistance programs: how they work and what they cost. Discusses chronic care and disease management among the uninsured. Analyzes the universal health care debate and makes recommendations. The Care of the Uninsured in America will attract a wide audience among professionals and graduate students in public and community health and health policy; clinicians and nurses who treat the uninsured; administrators and managers seeking a deeper understanding of the system; and policymakers and analysts seeking avenues for change.